The role of entrepreneurial orientation and social capital toward technology innovation among SMEs in Kurdistan (Global Business Management Review (GBMR), 2022)
The emergence of the fourth industrial revolution has made fundamental changes to technology, industries, and societal patterns and processes. SMEs are familiarizing themselves with new technological innovations to adapt to the current shifts. SMEs significantly contribute to economic progress by creating jobs, generating revenue, reducing poverty, and launching new ventures, especially in developing economies. However, the contribution of the SMEs in Kurdistan is limited due to the weak capacity to produce technological innovations and the inability to execute manufacturing processes effectively. So, the study aims to investigate the impact of Entrepreneurial Orientation (EC) and Social Capital (SO) on the Technological Innovation (TI) of Kurdistan SMEs in the Kurdistan region of Iraq. This study used the resource-based theory as the underlying theory for its presumptions, and its model was constructed using self-administered questionnaires. Three hundred forty-four business owners participated in this study, yielding a response rate of 68%. The results of the current study showed that social capital and entrepreneurial orientation both significantly and positively affect technological innovation. The study will contribute to technology innovation adoption among small industrial companies in Kurdistan and reduce potential setbacks for technology adoption, highlighting externally generated knowledge of entrepreneurial orientation and social capital.